IMPACT OF PUBLIC SERVICE AGENCY STATUS ON MANAGEMENT AND IMPROVEMENT OF HIGHER EDUCATION SERVICES: CASE STUDY AT BANDUNG STATE POLYTECHNIC - Awaliyah, Siti Aini Latifah; Nasir, Tatang Muh; Yudiyanto, Mohamad; Apandi, Taufik; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Public Service Agency (BLU) status provides financial management flexibility for state universities in Indonesia, including the Bandung State Polytechnic (Polban), to improve the efficiency and quality of educational services. This research aims to analyze the impact of BLU implementation on asset optimization, income diversification, and improving academic and non-academic services in Polban. This research uses a case study-based qualitative method, data was collected through in-depth interviews, observation and document analysis. The research results show that the implementation of BLU in Polban increases financial autonomy and enables more productive asset management, despite facing challenges in operational efficiency and asset management. In conclusion, the implementation of BLU in Polban has succeeded in improving service performance and financial independence, but requires regulatory support and strategic management to overcome existing obstacles.